Charles e Ray Eames: o casamento entre a razão e emoção no design - Caversan, Adriana Lima; Silva, José Carlos Plácido da [UNESP] (My University, 2013)
The rationalism appears as a philosophical current whose mental process and logic and evidenced, with the main characteristic of modern thought the method, the Bauhaus represents for the design the way the industry undressed the ornaments seeking the ideal of form and function. In a current contemporary design the emotional recovery in addition to the functions that an object can have, aesthetic, practical and symbolic, also the emotional identification, making review the methods. This article makes a relation of this context with the brilliantly that the couple Charles and Ray Eames, have created a method quite emotional for the creation of design, starting with the invention of the plywood and then with access to various technologies resulting from post-war, they created a very interesting process of building design combining art technique, producing seats that are ageless, found easily in the contemporary world.

O racionalismo surge como uma corrente filosófica, cuja operação mental e lógica é evidenciada. Sendo a principal característica do pensamento moderno o método, a bauhaus representa para o design a forma como a indústria se despiu dos ornamentos, buscando o ideal de forma e função. Numa corrente contemporânea, o design emocional retoma, além das funções que um objeto pode ter, estéticas, práticas e simbólicas, também as emocionais de identificação, fazendo rever os métodos. Este artigo faz uma relação deste contexto com a forma brilhante com que o casal Charles e Ray Eames, criou um método absolutamente emocional para a criação do design, iniciando, com a invenção do contraplacado, e depois com acesso a diversas tecnologias advindas do pós-guerra, um processo muito interessante de construção de design, aliando arte e técnica, produzindo assentos atemporais, encontrados facilmente no mundo contemporâneo.
Keywords: Reason; Design; Emotion; Razão; Design; Emoção